Oil-Price Boom and Real Exchange Rate Appreciation : Is there Dutch Disease in the Cemac? - Trevino, Juan (IMF Working Papers; Working Paper ;, 2011)
The paper employs a heuristic comparative approach suggested by Ismail (2009) to search for evidence of Dutch disease in oil-rich countries of the Central African Economic and Monetary Community (CEMAC). While these countries have benefitted from high international oil prices in recent years, they have also experienced relatively large real exchange rate appreciations, raising concerns regarding the presence of Dutch disease and casting doubts on their ability to achieve high growth and employment in the long run. To isolate from any dynamics related to the exchange rate regime, we focus on the 14 member countries that constitute the CFA franc zone. We separate them into net oil importers and net oil exporters and look at economic growth, the real exchange rate, and the agricultural and external sectors. Based on traditional models, our findings are broadly consistent with the presence of Dutch disease in the second group during the oil-price boom. Departing from these models yields mixed results, suggesting the need to employ a case-by-case approach.